The Impact of Brownfields on Residential Property Values in Post-Industrial Communities: A Study from the Eastern Part of the Czech Republic - Kamila Turečková; Stanislav Martinát; Jan Nevima; František Varadzin (Land, 2022)
Dilapidated, neglected, or abandoned sites and buildings (so-called brownfields) are frequently neither visually attractive nor aesthetically valuable. Indeed, neglected brownfields contribute to the emergence of both objective and subjective barriers to the social, economic, and environmental development of communities. We also know that the occurrence of decayed brownfields affect the prices of residential housing in their vicinity. In our paper, we seek to better understand the impact of brownfields on the perceived value of neighbouring properties. We are also keen to shed more light on the factors behind the allegedly undesirable impact of brownfields on property values. Our research is based primarily on data obtained from a survey of 1,152 respondents in ten municipalities situated at the eastern part of the Czech Republic, where neglected brownfields frequently occur. The findings are complemented by an analysis of sales of residential properties located in proximity to brownfield sites, to further confirm our preliminary survey results. The results confirmed that neglected brownfields tend to negatively affect the value of neighbouring residential properties. Our results also signal that the concentration of socially unacceptable behaviour is considered a key issue for distorting property prices around brownfields. Our analyses have confirmed that distance from a particular brownfield is one of the factors significantly influencing property prices. We claim that neglected brownfields create negative externalities that require public sector interventions and better planning. We urgently need more systematic support for brownfield regeneration to improve the quality of life of residents in affected communities.